FIRST RECORD OF OSTRACODS FROM THE UPPER SILURIAN TAMBOLAR FORMATION, ARGENTINE PRECORDILLERA (Ameghiniana, 2018)
Ostracods have been recovered from the upper levels of the Pachaco Facies of the Tambolar Formation of the Argentine Precordillera.Four species, two of which are new (Bollia sp. nov., Neothlipsura khiska sp. nov.), are described. An evaluation of the conodontfauna suggests an late Silurian (Pridoli) to possibly Early Devonian (earliest Lochkovian) age for the unit. The ostracod fauna is characterizedby the absence of dimorphic Palaeocopina, forms typically abundant during the Silurian, and by the presence of Tricornina, a thin shelledspinose genus, together with representatives of Binodicopina and Metacopina (Thlipsuroidea). The taxonomic composition of the ostracodscorresponds to the Assemblage III of the Eifelian Mega-Assemblage or to a “mixed assemblage”, suggesting a deep subtidal environmentclose to the area of the storm wave base. This interpretation is consistent with an external platform environment proposed by otherauthors based on a stratigraphic analysis. The presence of ostracod taxa such as Neothlipsura khiska sp. nov. and Tricornina? sp. suggests afaunal link with the palaeocontinent of Laurentia.